Reduction of dust removal off the surfaces of highways and warehouses of loose materials of PJSC ¾KRYVBASZALIZRUDKOM¿ (Ecological Bulletin of Kryvyi Rih District, 2019)
The problem of air pollution with dust in the conditions of PJSC ¾Kryvbaszalizrudcom¿ and the ways of its solution are considered. The use of special solutions for processing surfaces of highways and warehouses of loose materials for the purpose of improvement of the ecological situation at the enterprise and premises is analyzed.
Keywords: dust; bischofite; mineralization; road